Factors affecting university students’ satisfaction on online learning system - Tan, Sharon; Chuah, Francis; Hiram, Ting (2016)
This paper examines several internal and external factors affecting university students’ level of satisfaction towards online learning system. Field data collected from 282 students from one of the local management university. Data were analyzed using multiple regression analysis. The outcome of the analysis suggests that the proposed factors are vital predictors for students’ level of satisfaction in using university’s online learning system.